2022
DOI: 10.1038/s41598-022-20216-5
|View full text |Cite
|
Sign up to set email alerts
|

The interacting effects of irrigation, sowing date and nitrogen on water status, protein and yield in pea (Pisum sativum L.)

Abstract: Management for agronomic practices might improves growth and grain yield in pea. The main objective of this experiment was to assess the interacting effects of different irrigation regimes, sowing date and nitrogen fertilizer treatments on pea traits. We evaluated three irrigation regimes (50, 75, and 100% of the plant irrigation requirement), two sowing dates (February and March), and nitrogen [application of nitroregn (N1) and without nitrogen as control (N0)] in 2019 and 2020 under field conditions. Chlorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The minimum, optimum and maximum temperatures for the emergence, vegetation and generative periods have been put at 3˚C, 28˚C and 38˚C respectively [36]. In previous studies was shown to be higher yield in the March compared to February, and the reason for this was to be lower risk of early frost or cold damage in peas [37].…”
Section: Resultsmentioning
confidence: 99%
“…The minimum, optimum and maximum temperatures for the emergence, vegetation and generative periods have been put at 3˚C, 28˚C and 38˚C respectively [36]. In previous studies was shown to be higher yield in the March compared to February, and the reason for this was to be lower risk of early frost or cold damage in peas [37].…”
Section: Resultsmentioning
confidence: 99%
“…Pea plants exhibit adaptability to diverse soil and climatic conditions, facilitated by their relatively short growing season [ 5 , 6 ]. Despite its adaptability, pea cultivation faces challenges stemming from the crop’s high sensitivity to various abiotic stress factors.…”
Section: Introductionmentioning
confidence: 99%